An investigation of the benefit of using IT in the context of university students with ADHD. (2016) - Binhadyan, Bader; Wickramasinghe, Nilmini
Attention deficit hyperactivity disorder (ADHD) is estimated to affect approximately 11% of the university populations which make it the second most prevalent disorder among North American university populations. This disorder impacts such students when it comes to keeping up with academic loads, study skills, and social life. Technology has the capability to improve mental health services. In the last decade, Australia has become one of the leading countries in providing e-mental health services and so a study has been designed to investigate possibilities in this country. The study design outlined in this paper proffers a possibility for applying information communication technology (ICT) solution to facilitate the current treatment/management of ADHD in university students.